THE ISSUE OF SUCCESSION OF KHAN GOVERNANCE IN GOLDEN HORDE AND KAZAKH KHANATE (Journal of history, 2019)
In the article the issue of succession of khan governance in Golden Horde and Kazakh Khanate is considered. In the process of collapse of Golden Horde the governance in the state formed in its territory was in possession of Chingisids descendants of Zhoshy khan. This tradition continued in Kazakhstan until the beginning of the 19 century. Some signs of governing institutions in Golden Horde were stable and sustainable. They appeared during the process of collapse of Golden Horde in the regions where new states were formed. One of these parameters is khan governance issue. Along with the dynasty continuation of khan governance, the issues of ways of possession of the khan governance, inheritance, continuation of main attributes of khan governance is considered. For example, continuation of tradition of election of khan, appointment of most powerful candidate from ruling dynasty to khan governance.